Unusual Choanal Atresia in Children - Ibnu, Yunis Sucipta; Kristyono, Irwan (Folia Medica Indonesiana, 2022)
Highlights: • Unusual CA in a 5-year-old boy with paranasal sinuses malformation in the ORL-HNS. • Transnasal endoscopy posterior septectomy was successfully done. Abstract: Choanal atresia is a developmental failure of the nasal cavity to connect with the nasopharynx. The cause is either unilateral or bilateral nasal obstruction. Bilateral choanal atresia is a very rare condition and diagnosed soon after birth because neonates are obligate nasal breathers. Delayed diagnosis can cause death due to respiratory distress. The objective of this study was to report bilateral choanal atresia in 5-year-old boy who survived by breathing through his mouth using a simple tool made by his parent. It was a very rare condition because the posterior nasal cavity was covered by medial wall malformations of both maxillary sinuses which fused with the posterior nasal septum. The surgery method for this patient was posterior septectomy with transnasal endoscopic to create a neochoanae. The post-operative patient could breathe normally through his nose. Six weeks later, the nasal endoscopic evaluation indicated the patient's patent neochoana.